A bio-economic model for the ecosystem-based management of the coastal fishery in French Guiana. (28th February 2013) - Cissé, A.A.; Gourguet, S.; Doyen, L.; Blanchard, F.; Péreau, J.-C.
Abstract: This paper offers a theoretical and empirical model of ecosystem-based fishery management. A multi-species and multi-fleet model integrating Lotka–Volterra trophic dynamics as well as production and profit assessments is developed and applied to the coastal fishery of French Guiana. This small-scale fishery constitutes a challenging example with high fish biodiversity, several non-selective fleets and a potentially increasing local food demand due to demographic growth. The dynamic model is calibrated with 13 species and four fleets using monthly catch and effort data from 2006 to 2009. Several contrasted fishing scenarios including status quo, total closure, economic and viable strategies are then simulated. They are compared from the viewpoints of both biodiversity preservation and socioeconomic performance, assuming fixed landing prices and fixed costs. We show that fishing outputs, including food supply and fleet profitability, can be sustained on average but a loss of species cannot be avoided.